2017
DOI: 10.2174/1874364101711010059
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Refractive Procedures for the Treatment of Presbyopia

Abstract: Purpose:Refractive surgery has been in use for a long time and is evolving at a fast pace with several new corneal procedures being used for the correction of presbyopia. The purpose of this article is to give a comprehensive review of the literature to evaluate the outcome and success of different corneal refractive surgical procedures in presbyopic patients.Methods:We performed a comprehensive search on PubMed to identify published reports of the various procedures utilized in the past and present to correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 76 publications
0
7
0
1
Order By: Relevance
“…nondominant eye is made slightly myopic (mini or micro monovision) [12]. Reported success rates of PresbyLASIK vary; furthermore, the evidence is limited by a lack of standardized outcome measures and long-term follow-up [11,12].…”
Section: Key Pointsmentioning
confidence: 99%
“…nondominant eye is made slightly myopic (mini or micro monovision) [12]. Reported success rates of PresbyLASIK vary; furthermore, the evidence is limited by a lack of standardized outcome measures and long-term follow-up [11,12].…”
Section: Key Pointsmentioning
confidence: 99%
“…2,3,4,5,6 Previous studies have compared different types of presbyopic corrections and have suggested that PALs are the most acceptable solution. 7,8,9,10 A PAL is designed to provide continuous vision at all required viewing distances (distance, intermediate and near). 1,5 Progressive lenses ensure the optimal dioptric power for every distance that the presbyopic spectacle wearer requires, for smooth and uninterrupted vision without any visible lines of demarcation.…”
Section: Introductionmentioning
confidence: 99%
“…External ocular lenses, such as spectacles or contact lenses, are typically used to correct vision [1]. Ocular surgery and surgical devices, such as corneal inlays [3], multifocal or extended depth of field (EDOF) intra-ocular lenses [4][5][6] and refractive laser [7,8] can also be used as treatment options, but these are invasive procedures, they are expensive and some treatments can only treat one eye (monovision) with a loss of optical summation from binocular vision [1,[3][4][5][6][7][8]. Access to spectacles is also problematic in developing countries, where 94% of presbyopic subjects reside [2].…”
Section: Introductionmentioning
confidence: 99%